Complete Metabolic Response of Advanced Melanoma to Vemurafenib Assessed with FDG-PET-CT at 85 Hours. (May 2018) - Pascal, Pierre; Dercle, Laurent; Weyts, Kathleen; Meyer, Nicolas; Courbon, Fréderic
Abstract : Abstract: Vemurafenib improves the management of advanced melanoma due to selective inhibition of the mutated BRAF V600E kinase. FDG-PET-CT is a tool for the evaluation of the biologic impact of inhibiting mutant BRAF. With vemurafenib at day 15, all the patients had at least partial metabolic response. Reductions in uptake correlate with longer progression free survival. In this case, incomplete information provided by the patient led to the performance of his third PET 85 hours after the introduction of vemurafenib. This early case of complete metabolic response suggests that FDG-PET-CT is a useful marker of early biologic response to vemurafenib.